Time moving 100-fold slower: time distortion as a diagnostic clue in anti-NMDA receptor encephalitis - Risa Hirata; Hisashi Wada; Kazunori Yamamoto; Yuji Sogi; Hiroto Muzuta; Yu Isaka; Michitaka Funayama (BMC Neurology, 2025)
Abstract Background The primary symptoms in the early stages of anti-NMDA receptor encephalitis are psychiatric manifestations, making it difficult to distinguish from psychiatric disorders. While anti-NMDA receptor encephalitis requires a completely different treatment approach, the specific psychiatric features of the condition remain poorly identified. Although previous studies have suggested that altered perceptions may be characteristic, few case reports focus on altered perceptions of time or time distortion, a phenomenon closely linked to NMDA receptor dysfunction as seen in individuals using NMDA receptor inhibitors like ketamine and phencyclidine. In this report, we describe two cases of anti-NMDA receptor encephalitis manifesting pronounced time distortion in its early stages, which may serve as diagnostic clues for the early diagnosis and treatment of this potentially lethal condition. Case presentations Two cases of Anti-NMDA receptor encephalitis, both marked by significant time distortion in the early stages and showing near-complete recovery with immunotherapy, are presented in detail. In both cases, time distortion was the predominant symptom among the psychiatric manifestations. Case 1: A middle-aged man experienced a pronounced perception of time moving 100 times slower in the early stages, accompanied by feelings of detachment and auditory abnormalities. This time distortion persisted for over a year, even after other symptoms had fully resolved. Case 2: A young woman reported that time seemed to move two to three times slower in the early stages. Although she did not initially mention time distortion, she confirmed it when specifically questioned. Conclusions Our report suggests that time distortion, particularly the perception of time moving slowly, can be a distinguishing feature in the early stages of anti-NMDA receptor encephalitis. This unique characteristic, especially when occurring independently of other symptoms, is rare as a primary and isolated symptom in other conditions, making it useful for differentiation from time distortion in other psychiatric disorders. Additionally, since some patients may not spontaneously report time distortion, actively assessing this symptom during early evaluation could help improve diagnostic accuracy.